The narrow road to the deep north : a novel - Flanagan, Richard, 1961- (Knopf, 2014)
"A novel of love and war that traces the life of one man--an Australian surgeon--from a prisoner-of-war camp on the Thai-Burma Death Railway during World War II, up to the present"--